An approach to detect epileptic seizure using XAI and machine learning - Bijoy, Emam Hasan; Rahman, Md. Hasibur; Ahmed, Sabbir; Laskor, Md. Shifat (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2022.